Acoustic Phonons in Nanowires with Embedded Heterostructures. (13th October 2011) - Ayedh, Hussein M.; Wacker, Andreas
Abstract : Acoustic phonons are studied in finite nanowires based on the elastic continuum model. The phonon dispersion relations are compared for different types of approximations both for pure nanowires and nanowire heterostructures including cubic and wurtzite materials. We find that the isotropic approximation highly underestimates the frequency of torsional modes. The impact of heterostructures on the lowest modes is rather weak and can be described by an average of the different structure parameters.